Estudo das propriedades estruturais e eletrônicas de bundles de nanotubos de BN dupla camada sob pressão - Melo, Wesdney dos Santos (2011)
In this work we studied the structural and electronics properties (10; 0)@(17; 0) of double wall BN nanotubes bundle without intercalation and intercalated with the H2SO4 molecule, submitted to variations of hydrostatic pressure. For to study such properties we used the ab initio method employing density functional theory in the approach of the generalized gradient approximation for the exchange and correlation terms. All the simulations were performed using the SIESTA code. In the analysis of all results we observed that the traverse circular section of the nanotubos suffers a structural modification when the applied pressure around 1 GPa both system. Another structural change observed, both systems, appears around 10 GPa. The analysis the electronic properties was accomplished through the bands structure, where it was observed that the two systems considered are semiconductors, but with reduction in the energy gap. The analysis of the population of Mülliken, in the case of the doped system with H2SO4 molecule, shows that the nanotubes transfer charge to H2SO4 molecule, and the transference increases with pressure.